Cross-Functional Training of Front-Line Hotel Employees, In-Role and Extra-Role Job Performance, Customer Satisfaction, and Customer Loyalty: A conceptual Model Proposal - SUMANEEVA, Ksenia A.; ELUWOLE, Kayode Kolawole; AVCI, Turgay (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).07, 2019)
The purpose of this paper is to develop the theoretical conceptual model regarding benefits of cross-functional training of frontline hotel employees from interrelated departments of hospitality organizations for further investigation. This study aims to review the hospitality management literature and provide the conceptual model of cross-functional training and its connection to customer loyalty via the mediating role of individual job performance ( e.g ., in-role and extra-role employees’ job performance) and customer satisfaction in the hotel context. This paper identifies the gap within existing studies regarding consequences of frontline hotel employees’ cross-functional training and proposes the new conceptual model for the further investigation through extensive literature review of relevant literature. Hotel managers implement training programs to develop frontline hotel employees’ skills, motivate them to perform better and provide high-quality service to the customers. This paper proposes that cross-functional training of frontline hotel employees can be used to build strong coordination and integration between frontline hotel employees from interrelated hotel departments ( e.g ., front office, housekeeping, room service, F and B), increase employees’ awareness regarding other departments’ procedures, what, in turn, may significantly improve their individual job performance ( e.g ., in-role and extra-role performance), increase customer satisfaction and customers loyalty. This study attempts to fill the existing gaps in the literature regarding the benefits of cross-functional training by suggesting the new conceptual model regarding frontline hotel employees’ cross-functional training, and its link to frontline hotel employees’ in-role and extra-role job performance, customer satisfaction, and customer loyalty for the further investigation. This proposed conceptual model integrates contribution of three main parties of the hotel organization ( e.g ., supervisors, frontline hotel employees, and customers) as the proposed variables should be investigated by collecting data from different sources.